Investigation of Surface Charge at the Mineral/Brine Interface: Implications for Wettability Alteration - Mohammed, Isah; Al Shehri, Dhafer; Mahmoud, Mohamed; Kamal, Muhammad Shahzad; Arif, Muhammad; Alade, Olalekan Saheed; Patil, Shirish (Frontiers in Materials, 2022)
The reservoir rock is made up of different minerals, which contribute to the overall formation wettability. These minerals in their natural state differ in chemistry and structure, thus, behave differently in an environment of varying composition and salinity. These have direct implications for enhanced oil recovery due to water flooding, or wettability alteration due to long-term exposure to brine. With the reservoir rock being a complex system of multiple minerals, the control of wettability alterations becomes difficult to manage. One of the dominant mechanisms responsible for wettability alteration is the mineral surface charge, which is dependent on pH, and fluid composition (salt type and salinity). For the first time, the surface charge development of barite, dolomite, and feldspar minerals in native reservoir environments (accounting for the formation brine complexity) is presented. Also, the effect of oilfield operations (induced pH change) on minerals’ surface charge development is studied. This was achieved by using zeta potential measurements. Zeta potential results show that barite and dolomite minerals possess positively charge surfaces in formation water and seawater, with the feldspar having a near-zero surface charge. Furthermore, the surface charge development is controlled by the H+/OH- (pH), electrical double layer effect as well as ion adsorption on the mineral’s surfaces. These findings provide key insights into the role of fluid environment (pH, composition) and oilfield operations on mineral surface charge development. In addition, results show that careful tuning of pH with seawater injection could serve as an operational strategy to control the mineral surface charge. This is important as negatively charged surfaces negate wettability alteration due to polar crude oil components. Also, the design of an ion-engineered fluid to control the surface charge of minerals was implemented and the results show that reduction in the Ca2+ concentration holds the key to the surface charge modification. Surface charge modifications as evidenced in this study play a critical role in the control of wettability alteration to enhance production.